Out of the Ashes - Peterson, Tracie; Woodhouse, Kimberley 1973- (Minneapolis, Minnesota Bethany House, a division of Baker Publishing Group, 2018)
Katherine and Jean-Michel once shared a deep love that was torn apart by forces beyond their control. Reunited in the 1920s at the Curry Hotel in Alaska, have the years changed them too deeply to rediscover what they had? And when Jean-Michel's nightmares of war return with terrifying consequences, will faith be enough to heal what's been broken for so long?
Keywords: Man-woman relationships -- Fiction; Alaska -- Fiction; Christian fiction; Historical fiction; Romance fiction